2016
DOI: 10.1007/s13340-016-0272-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of predictors of insulin therapy in patients with gestational diabetes diagnosed according to the IADPSG criteria

Abstract: Aims and introduction It is helpful for both diabetologists and obstetricians to identify patients with gestational diabetes who require insulin therapy for glycemic control during pregnancy. The aim of the present study was to assess potential predictors of insulin requirement in patients with gestational diabetes. Materials and methods One hundred thirteen patients with gestational diabetes [mean age 34.2 ± 4.5 years; pre-gestational body mass index (BMI), 23.6 ± 6.0 kg/m 2 ] were included in this study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…We found that fasting abnormality was a positive predictor for insulin therapy, a result similar to other studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The mean fasting glucose among our women on insulin was higher than those who were on diet therapy, with no significant difference noted in the postprandial level.…”
Section: Discussionsupporting
confidence: 91%
“…We found that fasting abnormality was a positive predictor for insulin therapy, a result similar to other studies [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The mean fasting glucose among our women on insulin was higher than those who were on diet therapy, with no significant difference noted in the postprandial level.…”
Section: Discussionsupporting
confidence: 91%
“…Although the specificity of these studies largely varied (eg, location, sample size, screening methods, diagnostic thresholds), they consistently showed that as maternal BMI increased, so did the risk of being treated with insulin. 12–15 32 34 36–38 Regarding the associations between smoking and GDM treatment, some studies showed that more smokers were treated with insulin than lifestyle changes, 15 33 39 while others found an opposite relationship, 38 40 although the differences between groups in these studies were not reported to be statistically significant. A more recent study has reported that smoking was associated with a higher risk of insulin treatment, although this was relative to women without GDM and women with GDM not requiring insulin treatment combined in the same control group.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the incidence of requiring insulin therapy later in pregnancy was 52.5% in women with E-GDM and a pre-pregnancy BMI ≥25 kg/m 2 and/or a family history of DM. Previously, it was reported that higher pre-pregnancy BMI and a family history of T2DM were associated with later insulin therapy in GDM diagnosed using the IADPSG criteria (diagnosed after 24 gestational weeks) [28,29]. According to our criteria, women with a pre-pregnancy BMI ≥25 kg/m 2 and a family history of diabetes were assigned to the first trimester screening positive group and received an OGTT in the first trimester, resulting in most women with these risk factors being diagnosed with GDM before 24 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%